Notes on the “experience of jubilee self-congratulation” of V. I. Starostenko (towards the 90th anniversary) - Kobolev, V.P. (Geofizicheskiy Zhurnal, 2025)
This article is devoted to the significant milestones accomplished during the research career of the outstanding Ukrainian scientist-geophysics, V.I. Starostenko. His considerations on geophysics, science, Academy, some biographic data and thoughts have been presented.